The Students’ Creativity Level at Technical Department of Polimarin - Deri Herdawan (Sintuwu Maroso Journal of English Teaching, 2023)
There are many factors affecting the learning outcomes of education, one of which being creativity. The present research examined the students’ creativity level at technical department of Politeknik Maritim Negeri Indonesia. This descriptive research implemented the purposive sampling technique, involving 48 students as research subjects. A test consisting of 10 items to measure creativity was assigned to them. The data were analyzed using descriptive statistics and subsequently used to categorize the students based on their creativity level. The results revealed that the students had different creativity level (majorly high creativity in third semester students and low creativity in first semester students). Further details were elaborated and their relevance with teaching method selection was discussed. Future research should investigate how creativity interacts with certain teaching methods and moderates the learning outcomes.